2011
DOI: 10.1503/cmaj.101506
|View full text |Cite
|
Sign up to set email alerts
|

Industry involvement and baseline assumptions of cost-effectiveness analyses: diagnostic accuracy of the Papanicolaou test

Abstract: G iven the substantial impact of costeffectiveness analyses on public health policies, it is important to safeguard their robustness. However, most published costeffectiveness analyses report favourable incremental cost-effectiveness ratios, and industryfunded analyses are more likely to report desirable ratios.1 Some journals discourage cost-effectiveness analysis studies that have been conducted or funded by sponsors of the examined interventions.2 Examples exist in which cost-effectiveness analysis studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…These results are consistent with other studies assessing the relationship between the source of funding and the cost-effectiveness findings, specifically for oncologic drugs [2933], neuropsychiatric drugs [3436], venous thromboembolism pharmacologic prevention [37], drug-eluting stents [38], bisphosphonates for osteoporosis treatment [39], Pap tests for cervical cancer diagnosis [40]. They are also consistent with the CEAs submitted by manufacturers to health technology assessment agencies [5,6], and/or reviews selecting general cost-effectiveness studies [4,7,41,42].…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with other studies assessing the relationship between the source of funding and the cost-effectiveness findings, specifically for oncologic drugs [2933], neuropsychiatric drugs [3436], venous thromboembolism pharmacologic prevention [37], drug-eluting stents [38], bisphosphonates for osteoporosis treatment [39], Pap tests for cervical cancer diagnosis [40]. They are also consistent with the CEAs submitted by manufacturers to health technology assessment agencies [5,6], and/or reviews selecting general cost-effectiveness studies [4,7,41,42].…”
Section: Discussionsupporting
confidence: 90%
“…[60], [61] For example, Polyzos et al demonstrated that industry-sponsored CEAs assessing cervical cancer screening were more likely to exclude data sources presenting favourable results for existing technologies. [60], [61] We can consider our results in light of approaches for addressing parameter uncertainty, structural uncertainty, and methodological uncertainty in CEA modeling. Despite significant parameter uncertainty about the true value of the relative risk of breast cancer recurrence for AIs compared to tamoxifen, 44% of analyses we identified did not vary this critical parameter in even one-way sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Researcher respondents were particularly adamant that Canadian cervical cancer screening programs should shift towards primary hpv testing because the increase in sensitivity has the greatest impact on population health and health system spending, in the era of hpv vaccination 6,37 . Though not mentioned by interview respondents, some research questions whether this improvement might be exaggerated in the literature because of industry sponsorship of research 38 , which suggests that the shift may not be as "urgent" as some authors convey. In Canada, the Ontario government recently allocated funding for hpv testing in primary cervical cancer screening in their 2017 budget.…”
Section: Discussionmentioning
confidence: 99%